189 Real world experience on use of rituximab at regional refractory myasthenia gravis clinic in Birmingham. Issue 9 (12th August 2022) - San, Pyae Phyo; Jacob, Saiju; Sadalage, Girija; Roe, Alice
Abstract : Myasthenia gravis (MG) is a T-cell dependent B-cell mediated autoimmune disease targeting neuro- muscular junction. Rituximab is a chimeric CD20 monoclonal antibody which gives consistently high response rates in anti- Muscle Specific Kinase antibody positive MG. In contrast, the response rates were variable for anti-Ace- tylcholine Receptor antibody positive MG. NHS approved use of rituximab in specific circumstances in Myasthenia patients since 2019. Our NHS regional refractory MG clinic reviewed 15 patients who received Rituximab from 2019 to 2021. 14 were anti-AchR positive and 1 was anti-LRP4 positive. 7 had severe disease (MGFA Class IV/V). 12 had had prednisolone and at least 2 other immunosuppressants. 9 received standard Rituximab regime of 2 doses of 1 Gram 2-weeks apart. 6 received more than 2 doses due to unsatisfactory clinical improvement or relapse. From an average of 10% before treatment, periph- eral CD19+ B cell depletion to 0% was achieved in all although 3 had reappearance with one needing retreatment due to an accompanying clinical relapse. Outcome: Efficacy in MGFA Post-Intervention Status: 2 achieved Minimal Manifestations-3, 2 >50% Improved, 5 <50% Improved, 5 Unchanged and 1 Worse. Safety: None experienced side effects. Further analysis of steroid dose reduction and long-term outcome is currently being undertaken.